2016
DOI: 10.1177/0333102416653233
|View full text |Cite
|
Sign up to set email alerts
|

A phase IIb randomized, double-blind, placebo-controlled trial of ubrogepant for the acute treatment of migraine

Abstract: This trial supports ubrogepant's efficacy and provides further evidence that CGRP-RAs are viable options for the acute treatment of migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
167
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(174 citation statements)
references
References 30 publications
1
167
0
6
Order By: Relevance
“…53,90,91,130,148,167,184 More recently, RCTs using humanized monoclonal antibodies to CGRP or to the CGRP receptor have shown efficacy in patients with migraine. 20,21,54,55,173 For instance, a 12-week study in patients with episodic migraine demonstrated that the humanized monoclonal antibody galcanezumab reduced the frequency of migraine headache days with low incidence of adverse events.…”
Section: Calcitonin Gene–related Peptide Migraine and The Trigemmentioning
confidence: 99%
“…53,90,91,130,148,167,184 More recently, RCTs using humanized monoclonal antibodies to CGRP or to the CGRP receptor have shown efficacy in patients with migraine. 20,21,54,55,173 For instance, a 12-week study in patients with episodic migraine demonstrated that the humanized monoclonal antibody galcanezumab reduced the frequency of migraine headache days with low incidence of adverse events.…”
Section: Calcitonin Gene–related Peptide Migraine and The Trigemmentioning
confidence: 99%
“…45 Development of telcagepant was ultimately discontinued due to significant elevations of liver transaminase levels. 47 AEs were similar to placebo, with the most common being dry mouth, nausea, fatigue, dizziness, and somnolence. 46 Ubrogepant (MK-1602) has been studied for acute migraine treatment.…”
Section: Cgrp Receptor Antagonists (Gepants)mentioning
confidence: 84%
“…41,43 It was tolerated in patients with coronary artery disease 44 and stable angina. 47 Ubrogepant 100 mg was significantly superior to placebo for 2-hour pain freedom (25.5% vs 8.9%). 37 The development of another gepant, MK-3207, was also discontinued due to delayed liver test abnormalities.…”
Section: Cgrp Receptor Antagonists (Gepants)mentioning
confidence: 89%
See 1 more Smart Citation
“…Unfortunately, development was complicated by pharmacokinetic issues and for telcagepant and MK-3207 by hepatotoxicity. Ubrogepant is still under development for acute treatment [34] and atogepant for prevention (NCT02848326). Despite initial setbacks, these clinical trials have provided the proof of principle that targeting the CGRP pathway can effectively treat migraine.…”
Section: Clinical Trialsmentioning
confidence: 99%